Well-Being of Teachers: The Role of Efficacy of Teachers and Academic Optimism - Song, Kuo (Frontiers in Psychology, 2022)
In previous decades, teachers’ well-being has been at the center of researchers’ attention in several practical investigations in various subjects such as language learning. The objective of this review is to clarify this construct and add new information about the predominance of teachers’ well-being and organize factors impacting it. Nevertheless, among factors influencing the levels of well-being, the focus of this review is on two constructs, namely optimism “as a new concept in positive psychology”, societal theory, and collective school assets in education and teachers’ efficacy,as an individual source in teachers. This review tries to focus on the eminent role of teacher efficacy and optimism in the process of education and also clarify their consequences on teachers’ well-being. In a nutshell, this review can provide implications for language teaching participants in the academic context.